Brittleness index and its relationship with materials mechanical properties: Influence on the machinability of CAD/CAM materials - Thiago Soares Porto; Renato Cassio Roperto; Sorin Theodor Teich; Fady Fouad Faddoul; Fabio Antonio Piolla Rizzante; Sizenando de Toledo Porto-Neto; Edson Alves de Campos (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: The aim of this study is to evaluate the machinability of four CAD/CAM materials (n = 13) assessed by brittleness index, Vickers hardness, and fracture toughness and interaction among such mechanical properties. The materials selected in this in vitro study are Feldspathic ceramic [FC], Lithium-disilicate glass ceramic [LD], leucite-reinforced glass ceramic [LR], and nanofilled resin material [RN]. Slices were made from the blocks following original dimensions 14 × 12 × 3 mm (L × W × H), using a precision slow-speed saw device and then surfaces were regularized through a polishing device. Brittleness index and fracture toughness were calculated by the use of specific equations for each one of the properties. The Vickers hardness was calculated automated software in the microhardness device. One-way Anova and Pearson's correlation were applied to data evaluation. LD obtained the highest values for brittleness index and was not significantly different from FC. LR presented statistically significant difference compared with RN, which had the lowest mean. Vickers hardness showed LD with the highest average, and no statistical difference was found between FC and LR. RN presented the lowest average. Fracture toughness showed FC and LR not statistically different from each other, likewise LD and RN. The brittleness index, considered also as the machinability of a material, showed within this study as positively dependent on Vickers hardness, which leads to conclusion that hardness of ceramics is related to its milling capacity. In addition, fracture toughness of pre-sintered ceramics is compared to polymer-based materials.